2011
DOI: 10.1097/sap.0b013e31820d684d
|View full text |Cite
|
Sign up to set email alerts
|

Keloids Can Be Forced Into Remission With Surgical Excision and Radiation, Followed by Adjuvant Therapy

Abstract: We have treated keloids using a combination of surgical excision and postoperative irradiation. The objective of this study was to evaluate the results of our treatment over 12 years. From 1995 until 2006, we treated keloids using the aforementioned treatment. If we identified a sign of recurrence during the follow-up period, we started an intralesional injection of triamcinolone acetonide immediately. We selected 91 keloids for which we had more than 2 years of follow-up data for this study and assessed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…However, this method is not applicable for large or multiple keloids. Although surgical excision combined with postoperative radiotherapy is also a valuable modality for keloids, this method was not able to completely prevent recurrence . Keloid lesions contain a very high level of collagen fibers and this extracellular matrix protein was considered to be a target for keloid treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method is not applicable for large or multiple keloids. Although surgical excision combined with postoperative radiotherapy is also a valuable modality for keloids, this method was not able to completely prevent recurrence . Keloid lesions contain a very high level of collagen fibers and this extracellular matrix protein was considered to be a target for keloid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical excision combined with postoperative radiotherapy is also a valuable modality for keloids, this method was not able to completely prevent recurrence. 19 Keloid lesions contain a very high level of collagen fibers [2][3][4] and this extracellular matrix protein was considered to be a target for keloid treatment. However, Kang et al 20 reported that collagenase treatment was ineffective for keloid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously treated keloids using surgical excision and postoperative irradiation as a standard treatment 9 ; however, the radiosensitivity of the children is so high that hypoplasia following foot irradiation is inevitable. Therefore, intralesional steroid injections were substituted for radiation treatment as an additional postoperative treatment in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 5 injections of triamcinolone acetonide over a period of 16 months brought about a complete cure. Onwukwe 9 reported the successful outcomes of using methotrexate in the treatment of keloids. Low-dose methotrexate is widely used for rheumatoid arthritis and is used in both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…There are many treatments for keloids; steroid injections, steroid tape, surgery with postoperative irradiation and so on. Even if we carry out the operation and postoperative radiation to the keloid patients, the cure rate is 28~89% [3,[5][6][7][8], it depends on the individuals. To clarify the keloid pathogenesis will improve the treatments results.…”
Section: Introductionmentioning
confidence: 99%